Discovering Capital Structure Determinants for SAARC Energy Firms - Ghani, Erlane K.; Rehan, Raja; Salahuddin, Sultan; Hye, Qazi Muhammad Adnan (International Journal of Energy Economics and Policy, 2023)
Energy scarcity is the core drain for the South Asian economies. However, there is a lack of studies in relation to the capital structure determinants in the context of South Asian Association for Regional Cooperation (SAARC). Thus, this study is an attempt to explore the capital structure determinants of energy sector firms which are operating in the four large economies of the SAARC region that are Pakistan, India, Bangladesh and Sri Lanka. In this context, a total of 34 energy sector firms’ Panel Data is entailed over the period of 2007-2020. The six key capital structure determinants, namely asset tangibility, current ratio, return on equity, non-debt tax shield, annual gross domestic product are examined in relation to debt to total asset ratio. Deploying Panel Data Static models and Dynamic model via Generalized Method of Moments (GMM), the outcomes reveal that asset tangibility and current ratio are the most prominent determinants among all others. The significant role of profitability and tangibility through different estimators directly infers the relevance of Dynamic Trade-Off theory. The findings provide new ways for policy makers to construct parallel strategies which not only help out in overcoming the energy scarcity issues but also enhance regional level integration.